1997
DOI: 10.1006/viro.1996.8324
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the 3′ Terminal Sequence Recognized by the Rift Valley Fever Virus Transcription Complex in Its Ambisense S Segment

Abstract: A reconstituted transcription system composed of the Rift Valley fever phlebovirus (Bunyaviridae family) proteins L and N expressed via recombinant vaccinia viruses and an S-like model RNA containing the CAT gene in the antisense orientation, has been described previously by Lopez et al. (J. Virol., 1995, 69, 3972-3979). We extended the use of this in vivo system to determine the sequence at the 3' end of the ambisense S segment recognized by the transcription complex. A mutational analysis of the sequences at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 0 publications
1
33
0
Order By: Relevance
“…Thus, it will greatly improve the chances of developing urgently needed prophylactic measures and more feasible therapeutic interventions. The established helper virus system can already be used to modify the viral genome segments and study the impact on the viral replication cycle, as demonstrated before for other bunyaviruses (1,6,10,13,25,33,40). Insertions of genetic markers into the viral genome will later facilitate the identification of recombinant viruses and document reassortment events.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it will greatly improve the chances of developing urgently needed prophylactic measures and more feasible therapeutic interventions. The established helper virus system can already be used to modify the viral genome segments and study the impact on the viral replication cycle, as demonstrated before for other bunyaviruses (1,6,10,13,25,33,40). Insertions of genetic markers into the viral genome will later facilitate the identification of recombinant viruses and document reassortment events.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, deletion of the first 3Ј-terminal three nucleotides of the genome promoter of respiratory syncytial virus had no effect on promoter activity (7), whereas influenza A virus genome promoter lacking the first 3Ј nucleotides retained about 60% of wild-type promoter activity (21). Moreover, the 3Ј-terminal first two nucleotides of the S RNA of the phlebovirus Rift Valley Fever virus were not required for the transcriptional activity of the S genome promoter (34).…”
Section: Vol 79 2005mentioning
confidence: 95%
“…Among the family Bunyaviridae, the establishment of a reverse genetics system has been reported only for BUNV (5), while minigenome (or minireplicon) systems have been developed in BUNV (13), LACV (3), Crimean-Congo hemorrhagic fever virus (15), Hantaan virus (14), UUKV (16), and RVFV (1,21,26). In a typical minigenome system, virus-like RNA (minigenome) transcripts contain an internal open reading frame (ORF) of a reporter gene in place of a viral ORF sandwiched by untranslated regions (UTR) of viral RNA termini.…”
mentioning
confidence: 99%